Market policy and market Development: A comparison of dairy product consumption in Mombasa, Kenya and Dar-es-Salaam, Tanzania - Mullins, G.R. (Food and Agriculture Organization of the United Nations, 1995)
Past research on smallholder dairy production in Sub-Saharan Africa has generally focused on the technical challenges farmers face in producing, processing, and marketing their milk. An area which has been under-emphasized is the role that the policy environment plays in stimulating and facilitating sustainable dairy market Development. In this paper, the author highlights how policy can influence market Development by contrasting the dairy markets of Mombasa, Kenya and Dar-es-Salaam, Tanzania, two East African coastal cities with nearly identical ecological conditions, farming systems, cultural heritages and ethnic populations. What the two cities have not shared in common, however, has been their economic and agricultural policy environments, which the author argues here has lead to the dissimilar structures of their present day dairy markets. Comparisons of household dairy product consumption, product preferences, prices, sources, constraints and other primary data are used to establish the argument.